112 Specialist palliative and end of life timely intervention project (SPELTIP) on the emergency floor – outcomes from the first 20 weeks. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Edwards, Sarah; Keillor, Lisa; Murray, Karen; Kerslake, Stacey; Grant, Julia
Abstract : Background: The majority of deaths occur in hospital. Most hospitals have access to Specialist Palliative Care with a variable amount of provision. Most are designed to be reactive and responsive. A local audit in 2018 demonstrated that 89% of hospital deaths occurred following emergency admission. Clinical decision-making at admission did not always reflect the fact that the patient was at risk of dying. Opportunities to plan and involve patients in escalation decisions were missed and individualised planning was inconsistent. The aim was to improve the experience and outcomes for patients admitted with palliative and end of life care needs through role modelling, clinical support and education. Methods: A successful bid to Macmillan Cancer Support funded 2-year project for a proactive model of care with two Palliative Clinical Nurse Specialists (PCNS) based on the Emergency Floor. The Emergency Floor includes the Emergency Department and a variety of Acute Medical and Frailty wards. We wanted to evaluate the effectiveness of the PCNS service on staff and patients. Results: We report the first 20 weeks of the project, November 2019 to March 2020. The team had 336 contacts with 202 patients. 85% achieved their preference for place of care. The average length of stay was 3.75 days as opposed to 14 days for similar patients. Over 50% of patients did not need admission into the hospital from the Emergency Floor. Feedback has been extremely positive. Conclusion: Proactive specialist palliative care located at the point of admission improves the experience and outcomes for patients admitted with palliative and end of life care needs in an emergency. This work should influence how specialist services are provided in the future at a local and national level.